SYOK DAN PENANGANANNYA Yonny Herdyanto - HERDYANTO, YONNY (Arena, 2010)
ABSTRACT Shock is a serious condition that occurs when the cardiovascular system (heart and blood vessels) are not able to drain blood around the body in sufficient quantity. Shock is a clinical syndrome which has a characteristic form of hypotension, tachycardia, skin cold, pale and wet, hyperventilasi, changes in mental status and decreased urine formation. Shock is classified into several groups, namely: (1) cardiogenic shock (associated with heart defects), (2) hypovolaemic shock (due to decreased blood volume), (3) Shock anafilaktik (due to allergic reactions), (4) septic shock (associated with infection), (5) neurogenic shock (due to damage to the nervous system) Keywords: Shock